Los préstamos hipotecarios y su incidencia en la fijación de la pensión alimenticia. Propuesta alternativa. - Vásquez Guambaña., Juan Carlos (2024)
The present thesis entitled "Mortgage loans and their incidence in the determination of alimony. Alternative proposal", had the objective of carrying out a conceptual, doctrinal and legal study on the importance of considering mortgage loans for the acquisition or construction of housing where the child or adolescent is the main beneficiary, as a legal discount; mortgage loans are not usually a parameter to be considered at the time of setting alimony. However, if a parent has acquired a property through a mortgage loan and this significantly affects his or her ability to meet daily expenses and comply with alimony, it could be a factor to be considered in the negotiation or revision of alimony, since the courts consider factors such as income, expenses and socioeconomic conditions of the parties involved; therefore, it is intended to demonstrate the impact on alimony fixing in certain situations, since the determination of alimony varies according to the needs of the child or children. From the development of the investigation, it is known that the only admissible deduction to the income of the feeder is the deduction for payment of the contribution to the Social Security, and according to the results obtained in the surveys made to the lawyers in free practice, when the mortgage loans have been taken into account to fix the pension, it has been due to agreements reached by the parties involved; We were able to identify which rights of the minor are not covered through the payment of mortgage loans, and we analyzed the effects on the fed and the feeder when mortgage loans are not considered at the time of setting alimony; therefore, it is necessary to propose a reform to the parameters that are taken into account in the CONA for the elaboration of the Minimum Alimony Table.